The Chaos of Combat: An Overview of Challenges in Military Mild Traumatic Brain Injury Research - Davenport, Nicholas D. (Frontiers in Psychiatry, 2016)
Mild traumatic brain injury (mTBI), or concussion, is among the most common injuries affecting Veterans of recent combat deployments. Military mTBI differs from civilian mTBI in fundamental ways that make assessment and diagnosis difficult, including a reliance on retrospective self-report and the potential influence of comorbid psychopathology. These unique features and their implications for research and clinical practice are summarized, and neuroimaging studies are discussed in the context of these complicating factors.